PREDICTIVE VALUE OF SERUM ALBUMIN LEVELS FOR PROGNOSIS OF SEVERE SEPSIS IN LATE PRETERM NEONATES ADMITTED IN NICU (Journal of Medical & Health Sciences Review, 2025)
Neonatal sepsis is still a common problem in NICU, and late preterm babies, aged 34 to 36 weeks postmenstrual age are still at high risk due to their immature immunologic system. The identification of the early risk is crucial in the management of patients, but the previously established biomarkers including C-reactive protein (CRP) and Procalcitonin are associated with some drawbacks that affect the accuracy of risk prediction. The aim of this work is to know whether serum albumin levels in LPPN with severe sepsis admitted to NICU in CMH Abbottabad are useful in predicting mortality rates. Randomized controlled clinical trial was conducted during one year, with 100 late preterm neonates with severe sepsis. Serum albumin level was tested on admission, and its association with mortality, length of stay in NICU and mechanical ventilation, and MODS was also determined. The authors found out that the overall mortality rate was higher among neonates with hypoalbuminemia of